Math, asked by royshobha02, 4 months ago

34-65(67+87)×{69+65}+67×56​

Answers

Answered by chiggi2k03
2

Answer:

Given:     34 - 65 (67+ 87)× {69 + 65} + 67 × 56​

now,

⇒            34 - 65 ( 154 )× { 134 } + 67 × 56​

      (∵ as 67 + 87 = 154 and 69 + 65 = 134)

⇒          - 31 ( 154) × { 134 } + 67 × 56

              (∵ as 34 - 65 = - 31)

⇒          - 4,774 × { 134 } + 3,752

     ( ∵ as 31 × 154 = - 4,774 and 67 × 56 = 3752)

⇒           - 6,39,716 + 3752

    ( ∵ as -4774 × 134 = - 6,39,716)

⇒           -6,35,964

   ( ∵ as - 6,39,712 + 3752 = -6,35,964)

∴ So the correct answer is -6,35,964

plz mark this as brainliast.    

Similar questions